2004
DOI: 10.1158/0008-5472.can-04-2201
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide, a Mediator of Inflammation, Suppresses Tumorigenesis

Abstract: Inflammation influences the development of cancer. The nitric oxide synthase (NOS2) is induced by inflammatory cytokines, e.g., tumor necrosis factor ␣ and interleukin 1␤, and produces nitric oxide (NO ⅐ ), a critical mediator of the inflammatory response. Because p53 governs NO ⅐ production by transcriptionally transrepressing NOS2, we used a genetic strategy to determine whether NO ⅐ and p53 cooperatively regulate tumorigenesis. Lymphomas developed more rapidly in p53؊/؊NOS2؊/؊ or p53؊/؊NOS2؉/؊ mice than in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
68
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 34 publications
(27 reference statements)
7
68
0
Order By: Relevance
“…NO is known to be involved in diverse processes in numerous physiological and pathophysiological conditions; previous studies have suggested that NO can exert a negative effect on the (10,(12)(13)(14)(15)(16)(17)(18). However, studies concerning the effects of NO on HCC cells are rare.…”
Section: Discussionmentioning
confidence: 99%
“…NO is known to be involved in diverse processes in numerous physiological and pathophysiological conditions; previous studies have suggested that NO can exert a negative effect on the (10,(12)(13)(14)(15)(16)(17)(18). However, studies concerning the effects of NO on HCC cells are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage-derived NO is essential for the suppression of some tumors (54). Recent studies have shown that there is a higher incidence of lymphomas in p53/NOS-2 double knockout mice (55). Yet there was a significant delay in the onset of tumors in p53 Ϫ/Ϫ mice that were fed TEMPOL, an SOD mimetic (56).…”
Section: Discussionmentioning
confidence: 99%
“…NO ⅐ has potent anti-tumor and anti-atherosclerotic effects that are closely associated with its ability to block cell proliferation (17,20). This activity of NO ⅐ has been ascribed to both cGMP-dependent and -independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO ⅐ ) regulates a wide range of cellular activities including gene expression (12)(13)(14)(15)(16), cell proliferation (17,18), and apoptosis (19) that are closely linked to its anti-tumor and anti-atherosclerotic properties (17,20). Using a microarraybased approach in soluble guanylate cyclase-deficient cells, we recently demonstrated that NO ⅐ predominately regulated a large set of cell cycle genes independent cGMP (15).…”
mentioning
confidence: 99%